Engaging with the State: Considering the "Progressive Potential" of Feminist Service Provision - Boucher, Lisa Mae (Atlantis)

(untitled) (Mount Saint Vincent University, 2010)
Citing the possibility of co-optation, some activists and scholars argue that feminist organizations should avoid a funding relationship with the state. This article explores the implications of such engagement. I argue that feminist organizations must continue to pressure the state to support the third sector in a meaningful way.